Maximum Power Point Tracking in PV System with Industry Applications - Rajendra Aparnathi; Ved Vyas Dwivedi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
The paper work is the new maximum power point tracking method using in voltage controller in photo-voltaic system for Stand-Alone industry Applications with battery energy storage. The output of the PV array is unregulated DC supply due to change in weather conditions. The maximum power is tracked with respect to temperature and irradiance levels by using DC-DC converter. The perturbation and observes algorithm is applied for maximum power point tracking (MPPT) purpose. This algorithm is selected due to its ability to withstand against any parameter variation and having high efficiency.  The solar cell array powers the steady state energy and the battery compensates the dynamic energy in the system. The aim of the control strategy is to control the SEPIC converter and bi-direction DC-DC converter to operate in suitable modes according to the condition of solar cell and battery.DOI: http://dx.doi.org/10.11591/ijpeds.v3i4.4549